Relação entre a reação emocional à propaganda em mídias sociais e a avaliação da marca - Hahn, Ivanete Schneider (2013)
The internet has changed the way that consumers interact with each other and with companies. Social media appear as a new communication channel for business and enabling closer interaction between enterprises and consumers. The literature explains that the social media has a vital role in the promotion mix and companies can interact with consumers through online platforms (Facebook, Twitter, MySpace and others). Therefore, companies can no ignore the phenomena of social media, because it have become a tool for consumers expose their perception of products and services. This study aimed to evaluate the relationship between the emotional response to advertising on social media (Facebook) and the evaluation of the Coca-Cola brand, under the influence of technology readiness and consumers trust. The methodological procedures used to obtain answers to the objectives that guided this study followed the steps of the survey method, by surveying a cross-sectional, exploratory and descriptive study. To assess the relationship between different variables, we used the technique of structural equation modeling. The population was composed of all Brazilians, social media users, subscribers on Facebook. We obtained a total of 1,196 respondents, and of these, 1,037 are valid questionnaires. The choice of brand Coca-Cola gave up because is considered the most valuable in the world for 13 consecutive years and the most followed brand on Facebook worldwide and the second most followed in Brazil. The confirmation of the properties of unidimensionality, reliability, convergent and discriminant validity of the constructs permitted to propose and validate an integrated model, considered as hybrid. The hybrid model tested 48 variables and 118 estimated parameters. The results show that: (1) the emotional reaction to advertising on social media has a positive and direct influence on the Coca-Cola brand evaluation; (2) consumer trust exercised direct and positive influence on brand evaluation and emotional reaction to advertising on social media; and (3) the technology readiness has not a significant influence on the emotional reaction to advertising on social media. We concluded that it is possible to determine consumer trust as the most important variable to a positive emotional reaction to advertising on social media and a positive brand evaluation.